Computer science : an overview. - Brookshear, J. Glenn, 1944-; Brylow, Dennis, ....-; Smith, David Timothy, 1958- (Boston : Addison-Wesley, 2012)
Computer Science: An Overview uses broad coverage and clear exposition to present a complete picture of the dynamic computer science field. Accessible to students from all backgrounds, Glenn Brookshear uses a language-independent context to encourage the development of a practical, realistic understanding of the field. An overview of each of the important areas of Computer Science (e.g. Networking, OS, Computer Architecture, Algorithms) provides students with a general level of proficiency for future courses.